Colorectal cancer: a qualitative study of coping strategies used by survivors, with associated social determinants - Antonio González-Herrera; Enriqueta Pujol-Ribera; Magdalena Esteva; Lorena Ruiz-Marcos; Sebastià March (BMC, 2023)
Abstract Background Colorectal cancer survivors have to develop coping strategies during the diagnosis and survivorship period. This study aims to identify coping strategies in patients with colorectal cancer, in particular the differences between coping strategies during the disease and throughout survival. It also aims to investigate the impact of some social determinants on coping strategies and critically reflect on the influence of positive psychology. Methods Qualitative study with in-depth interviews of a purposive sample of 21 colorectal cancer survivors in Majorca (Spain), developed between 2017-2019. Data was analysed using interpretive thematic analysis. Results We observed different coping strategies during the stages of disease and survival. However, striving toward acceptance and adaptation when facing difficulties and uncertainty, predominate in both stages. Confrontational attitudes are also considered important, as well as encouraging positive rather than negative feelings, which are considered unhelpful and to be avoided. Conclusions Although coping during illness and survival can be classified into common categories (problem and emotion-centred strategies), the challenges of these stages are faced differently. Age, gender and the cultural influence of positive psychology strongly influence both stages and strategies.